Особистість у кіберкультурі (до питання про кіберсоціалізацію людини) - Івушкіна, О.В.; Сілютіна, І.М. (Культура народов Причерноморья, 2013)
Розглядається проблема формування й існування особистості у просторі кіберкультури. Кіберкультура аналізується як форма існування сучасної масової культури інформаційного суспільства, котра заснована на комунікативній практиці віртуальної взаємодії. Виявляється специфіка кіберпростору та висвітлюються особливості його естетичної предметності. Розглядається симулятивно-ризоматична форма знакових конструкцій віртуального світу кіберкультури. Рассматривается проблема формирования и существования личности в пространстве киберкультуры. Киберкультура анализируется как форма существования современной массовой культуры информационного общества, которая основана на коммуникативной практике виртуального взаимодействия. Выявляется специфика киберпространства и освещаются особенности его эстетической предметности. Рассматривается симулятивно-ризоматическая форма знаковых конструкций виртуального мира киберкультуры. The problem of personality’s formation and existence in cyber-cultural environment is considered in the context of the construction of social individual subjectivity in modern culture by means of discourses and valuable vectors of mass culture. Cyber-culture seems to be the form of the existence of a modern mass cultural information society, which is based on the communicative practice of virtual interaction. This practice is realized due to the syncretism form of the computer – symbolic Internet environment, the structure – functional configurations of which open them in the form of reasonable information units. Cyber environment reveals it as a technological total combination of communicative virtual nets creating conditions for synchronized interaction of individuals and groups in particular virtual continuity. Cyber environment influence on people is defined by the esthetic subject of a simulative reasonable form of symbolic designs of virtual reality. The symbols functioning in cyber environment and their exit beyond the virtual reality boundaries are considered to be very characteristic for modern type culture which is aimed at the religious de- mythology and creation of the esthetic mythology.